Book Review: Die Knochen- und Geweihgeräte der Feddersen Wierde by Katrin Struckmeyer - Wietske Prummel (EXARC Journal)
The purpose of this book, which was originally presented as a dissertation at Hamburg University, is to present the 1,293 bone, antler, horn and ivory tools that were found at the terp settlement Feddersen Wierde in the coastal area of Lower Saxony, Germany, and to decide on the possible functions of the tools.